A novel nomogram to predict all‐cause readmission or death risk in Chinese elderly patients with heart failure - Mengxi Yang; Liyuan Tao; Hui An; Gang Liu; Qiang Tu; Hu Zhang; Li Qin; Zhu Xiao; Yu Wang; Jiaxai Fan; Dongping Feng; Yan Liang; et al. (ESC Heart Failure)
Abstract Aims Elderly patients with heart failure (HF) are associated with frequent all‐cause readmission or death. The present study sought to develop an accurate and easy‐to‐use model to predict all‐cause readmission or death risk in Chinese elderly patients with HF. Methods and results This was a prospective cohort study in patients with HF aged 65 or older. Demographic, co‐morbidity, laboratory, and medication data were collected. A Cox regression model was used to identify factors for the prediction of readmission or death at 30 days and 1 year. A nomogram was developed with bootstrap validation. Of the included 854 patients, the cumulative all‐cause readmission and mortality rates were 10.5% and 11.6% at 30 days and 34.9% and 19.7% at 1 year, respectively. The independent risk factors associated with both 30 day and 1 year readmission or death were older age, stroke, diastolic blood pressure < 60 mmHg, body mass index ≤ 18.5 kg/m2, lower estimated glomerular filtration rate, and BNP > 400 pg/mL (all P < 0.05). Anaemia, abnormal neutrophils, and admission without angiotensin‐converting enzyme inhibitors/angiotensin receptor blockers were the specific independent risk factors of 30 day all‐cause readmission or death (all P < 0.05), whereas serum sodium ≤ 140 mmol/L and admission without beta‐blockers were the specific independent risk factors of 1 year all‐cause readmission or death (all P < 0.05). The C‐index of the 30 day and 1 year diagnosis prediction model was 0.778 [95% confidence interval (CI) 0.693–0.862] and 0.738 (95% CI 0.640–0.836), respectively. Conclusions We developed accurate and easy‐to‐use nomograms to predict all‐cause readmission or death in Chinese elderly patients with HF. The nomograms will assist in reducing the all‐cause readmission and mortality rates.